2001
DOI: 10.1152/ajpregu.2001.280.5.r1332
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone stimulates pancreatic growth in congenitally CCK-A receptor-deficient OLETF rats

Abstract: We examined the effect of troglitazone treatment on pancreatic growth in the CCK-A receptor-deficient Otsuka Long-Evans Tokushima fatty (OLETF) rat, an animal model for type 2 diabetes mellitus. A troglitazone-rich diet (0.2%) was given from 12 to 28 wk of age or from 12 or 28 wk of age to 72 wk of age. Fasting serum glucose concentrations in control OLETF rats increased progressively with age, which was almost completely prevented by troglitazone treatment. Insulin levels in serum and pancreatic content in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…However, several studies have demonstrated that oral administration of camostat prevents the development of diabetes and pancreatic fibrosis in WBN/Kob rats without affecting [16,17] or even increasing body weight [18]. Moreover, we have found in our previous studies that impairment of insulin secretion appears before the onset of abnormal lipid metabolism in OLETF rats [3,35]. Although these results suggest that the effects of camostat in OLETF rats are unlikely to be solely caused by weight loss or failure of weight gain, it is difficult to rule out the scenario of camostat-induced reduction of visceral adipose deposits as a cause of improved b-cell function.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, several studies have demonstrated that oral administration of camostat prevents the development of diabetes and pancreatic fibrosis in WBN/Kob rats without affecting [16,17] or even increasing body weight [18]. Moreover, we have found in our previous studies that impairment of insulin secretion appears before the onset of abnormal lipid metabolism in OLETF rats [3,35]. Although these results suggest that the effects of camostat in OLETF rats are unlikely to be solely caused by weight loss or failure of weight gain, it is difficult to rule out the scenario of camostat-induced reduction of visceral adipose deposits as a cause of improved b-cell function.…”
Section: Discussionmentioning
confidence: 60%
“…During pancreatic injury, PSCs are activated by proinflammatory cytokines such as tumor necrosis factor a (TNF-a), IL-1, and IL-6 [9] and transform into a myofibroblastic phenotype, exhibiting positive staining for a-smooth muscle actin (a-SMA), a marker of activated PSCs [2,[8][9][10]. These results suggest that induction of IL-1b in the islets is involved in islet destruction and that activation of PSCs in response to proinflammatory cytokines contributes to the development of pancreatic fibrosis and atrophy in OLETF rats [1][2][3].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We and other groups have reported fi nding that the TZD troglitazone contributes to the prevention of the progression of chronic pancreatitis in a rodent model of chronic pancreatitis by inhibiting ECM production. [57][58][59][60][61]63 TZD has also been shown to stimulate pancreatic growth in the congenitally cholecystokinin-A receptor defi cient OLETF rat, not only by reducing insulin resistance and potentiating insulin action but also by suppressing infl ammatory changes in the pancreas. 60 The levels of infl ammation marker within the pancreas [myeloperoxidase (MPO) activity, TGF-β1] and in the circulation (IL-6, soluble TNFR1) decrease when mice with chronic pancreatitis induced by repeated injections of cerulein are treated with TZD.…”
Section: Peroxisome Proliferator-activated Receptor G Ligandmentioning
confidence: 99%
“…[57][58][59][60][61]63 TZD has also been shown to stimulate pancreatic growth in the congenitally cholecystokinin-A receptor defi cient OLETF rat, not only by reducing insulin resistance and potentiating insulin action but also by suppressing infl ammatory changes in the pancreas. 60 The levels of infl ammation marker within the pancreas [myeloperoxidase (MPO) activity, TGF-β1] and in the circulation (IL-6, soluble TNFR1) decrease when mice with chronic pancreatitis induced by repeated injections of cerulein are treated with TZD. 61 In an in vitro study, TZD was found to inhibit ECM production and PDGF-stimulated cell proliferation by inducing G1 cell-cycle arrest, 62 but the precise mechanism of the antifi brogenic action of TZD is not fully understood.…”
Section: Peroxisome Proliferator-activated Receptor G Ligandmentioning
confidence: 99%